Relevansi Konsep Pembelajaran Perspektif Ibnu Khaldun pada Pembelajaran Bahasa Arab Era Modern - Ratih Haryati; Muhammad Jailani; Muhammad Fadli Ramadhan (Al-Jawhar : Journal of Arabic Language, 2023)
In the rapidly evolving digital era, traditional teaching methods continue to dominate, particularly in Arabic language learning. However, the origins of these methods often remain unknown. This descriptive qualitative research with the type of literature research aims to analyze the reverence between the concept of learning according to Ibn Khaldun's thoughts with modern Arabic language learning. The primary data source is the book Muqqadimah by Ibn Khaldun, while secondary data sources are various literatures and previous studies such as books, documents, articles, and various other sources related to the research subject. The findings in this study indicate that the concept of learning theory offered by Ibn Khaldun is Malakah and Tadrij. Overall the learning methods offered amounted to 13 methods, including the tadarruj method (phasing), tikrari method (repetition), al-qurb wa al-muyanah (method of affection), the method of determining age maturity in learning the Qur'an, the method of physical and psychological adaptation of students, the method of matching the development of student potential, the method of mastering one field, the method of avoiding book summaries (ikhtisar at-turuk), discussion and dialogue, the method of teaching Arabic, the method of widya wisata (rihlah), the method of tadrib (practice/exercise), and media-based learning methods. After the analysis, researchers found 9 learning methods of Ibn Khaldun that have relevance to Arabic language learning methods in the modern era, namely the method of tadarruj (gradual), tikrari (repetition), al-qurb wa al-muyanah (method of affection), the method of physical and psychological adaptation of students, discussion and dialogue, Arabic language teaching methods (special), the method of widya wisata (rihlah), the method of tadrib (practice/exercise), and media-based learning methods. It can be concluded that Ibn Khaldun's learning concept is relevant to Arabic language learning in the modern era which is oriented towards increasing competence and demanding active student-centered learning.